2009
DOI: 10.1002/lt.21719
|View full text |Cite
|
Sign up to set email alerts
|

Designated liver transplant anesthesia team reduces blood transfusion, need for mechanical ventilation, and duration of intensive care

Abstract: It was the area of manufacturing in which the idea of continuous quality improvement (CQI) originated and developed to what we consider a highly efficient model for all industries today. [1][2][3][4][5][6] Since the 1980s, when the cost of healthcare began rising faster in the United States than the cost of living, quality issues have gradually gained importance for the medical industry and the government. Furthermore, a systematic assessment of healthcare by the Institute of Medicine in 1999 revealed shocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…Our center also has a dedicated liver anesthesia team for all transplant cases. There is significant literature that shows that having a dedicated LT anesthesia team influences the number of blood transfusions, number of laboratory tests performed, length of postoperative ventilation, length of ICU stay, and the rate of postoperative complications as well as mortality . Whether or not there is an association between DCD outcomes and dedicated LT anesthesia teams needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Our center also has a dedicated liver anesthesia team for all transplant cases. There is significant literature that shows that having a dedicated LT anesthesia team influences the number of blood transfusions, number of laboratory tests performed, length of postoperative ventilation, length of ICU stay, and the rate of postoperative complications as well as mortality . Whether or not there is an association between DCD outcomes and dedicated LT anesthesia teams needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…By addressing various aspects of the LT service, fostering strong multidisciplinary relationships and implementing evidence based protocols, Hevesi et al [125] were able to deliver improvements in patient outcomes. Transfusion rates, ventilator days and LOS fell dramatically following the introduction of their quality improvement measures ( Figure 11).…”
Section: The Secret Ingredientmentioning
confidence: 99%
“…The inclusion of administrative tasks in the recommendations for directors differs from the recommendations for other UNOS/OPTN physician leadership positions. The ASA included these tasks after evidence suggested that consolidated anesthesia liver transplant teams had better recipient outcomes . The study reported additional educational activities and interdisciplinary communication as key factors in improving the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…The Membership and Professional Standards Committee of the Organ Procurement and Transplantation Network (OPTN)/United Network for Organ Sharing (UNOS) has approved a new bylaw recommending that each transplant center appoint a director of liver transplant anesthesia . This change is in response to evidence that anesthesiologists significantly influence liver transplant recipient outcomes and resource utilization but do not have uniform liver transplant experience or education …”
mentioning
confidence: 99%